2004
DOI: 10.1128/aem.70.9.5679-5681.2004
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role for Fish in Transmission of Mycobacterium ulcerans Disease (Buruli Ulcer): an Environmental Study

Abstract: This study reports a potential role that fish may play in the transmission of Mycobacterium ulcerans disease (Buruli ulcer). Fish found positive for M. ulcerans DNA all appear to feed on insects or plankton and are believed to concentrate M. ulcerans from this usual food source. These observations provide additional data supporting our previous hypothesis on sources of M. ulcerans and modes of transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 11 publications
2
64
1
Order By: Relevance
“…MIRU loci might be hot spots for transcriptional errors, leading to a faster adaptation to environmental changes than that caused by random mutations. M. ulcerans is well adapted to a variety of natural reservoirs, such as aquatic insects (21,29) and other aquatic organisms such as fish or snails (8,28). This might be due to the protective mininiche that is created by mycolactone (22).…”
Section: Discussionmentioning
confidence: 99%
“…MIRU loci might be hot spots for transcriptional errors, leading to a faster adaptation to environmental changes than that caused by random mutations. M. ulcerans is well adapted to a variety of natural reservoirs, such as aquatic insects (21,29) and other aquatic organisms such as fish or snails (8,28). This might be due to the protective mininiche that is created by mycolactone (22).…”
Section: Discussionmentioning
confidence: 99%
“…Those studies have relied solely on detection of IS2404 as evidence for M. ulcerans, based on a report showing that IS2404 was absent from 48 species of mycobacteria obtained from a laboratory collection (27). IS2404 PCR has been used to demonstrate the presence of M. ulcerans DNA in fish (10), frogs, many species of insects, snails, and a large range of aquatic samples from Africa (19,22 (31,35). In the past few years investigators have suggested that M. marinum isolates from humans are genetically different than isolates from poikilothermic species.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong association between the occurrence of M. ulcerans infection in humans and slow-flowing or stagnant water bodies (Marsollier et al, 2007;Portaels et al, 1999;Roberts & Hirst, 1997;Ross et al, 1997;Stinear et al, 2000a). Aquatic snails (Marsollier et al, 2004), fish (Eddyani et al, 2004) and water bugs (Marsollier et al, 2002) are currently being discussed as passive and active hosts, respectively. However, the exact mode of transmission of Buruli ulcer has remained a mystery, partly because no genetic fingerprinting tool is available for micro-epidemiological analysis of infection chains.…”
Section: Introductionmentioning
confidence: 99%